Perceptions of Economic Development and Its Social Impact - Anugrah, Edhib Harits (Generasi Sains Indonesia, 2024)
Using ideological contextualization, this work explores how people in Palu, Central Sulawesi, experience economic development and its resulting social change across the socio-economic strata. In a quantitative manner, this study aimed at assessing some opinions among residents of the USA classified among the different income groups; growth economy; social injustice; social cohesion; and the decline of traditional morality. The study also shows that although higher income groups are more likely to embrace economic development than negative its lower income groups experience social vices, inequality and rejection of modernity. Furthermore, the loss of the traditional value system and decline of solidarity, which both pale in comparison to the changes that the urbanization of Palu has brought to the participants in the field of study, are mentioned. The study helps to fill the gap in the literature on how various social groups are affected by economic development of mid-size cities and contributes to the international understanding of issues of urban development. That is why, according to the study, without liberationist policies, the process of economic growth only intensifies divisions within society and deepens existing fissures. These findings have policy implications for the policy makers who wish to foster balanced and inclusive development in such urban environments.